Effect Economic Value Added and Market Value Added to Stock Return Sub-Sector Cement Industry on BEI 2019-2023 - Diana Riyana Harjayanti; Risma Marliana; Ifa Nurmasari; Dony Oktariswan (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
The purpose of this study is to determine the effect of Economic Value Added (EVA) and Market Value Added (MVA) on stock return in manufacturing companies sub-sector cement industry listed on the Indonesia Stock Exchange period of 2019 – 2023. This research was conducted using a quantitative analysis method. This study using panel data regression analysis calculate in Eviews 13 program. Results of study shows that partially Economic Value Added (EVA) on Stock Return with value t-value 1.188 with a positive direction of < ttable 2.048 and a significant value of 0.2475 > 0.05 which means that Economic Value Added does not have a significant effect on stock return especially in manufacturing companies-sub sector cement industry period 2019 - 2023. And partially Market Value Added (MVA) to the Return of Stocks with a calculated value of t-value -3.990 with a negative direction > ttable 2.048 and a significant value of 0.0006 < 0.05, This means that Market Value Added (MVA) has a significant effect on stock returns, especially in manufacturing companies-sub sector cement industry period the 2019 - 2023 period. And simultaneously (together) Economic Value Added (EVA) and Market Value Added (MVA) have a significant effect on Stock Return with a calculated value of F-value 6.1407 with a positive direction > Ftable 2.510 and 0.0004 < 0,05. And also the result of the determination coefficient value (Adjusted R Square) of 0.553 or 55.3% and the remaining 44.7% was influenced by other variables outside the research model.